Memory Errors in Eyewitness Identification Testimony - P. Budyakova, Tatyana (International Journal of Psychosocial Rehabilitation, 2020)
Purpose. The history of forensics knows a great number of misidentifications of suspected criminals. Certain attempts to study the reasons for identification errors were made in psychology; some phenomena were even described, but the whole range of such errors has not been established yet.Methodology. We used collages showing famous people (Saddam Hussein, Britney Spears, Mireille Mathieu, Leonardo DiCaprio) with two identification-significant features altered, such as hairstyle (for men and women) and facial hair (for men). Human subjects had to identify the people shown in the collages. The first phase of the study took place in 2003, the second one in 2015, each with different groups of subjects. The time interval enabled us to determine how time and decreased or increased popularity affected identification accuracy.Results. It is found that eyewitness identification accuracy is affected by the verbalization of identification features. Verbalization is a demand to formulate the identifying features the witness relies upon during the identification process. Recognition of previously familiar and unfamiliar faces is based upon different principles, as in addition to recognizing individual features of a familiar face, the witness also perceives their specific configuration. In cases with a considerable time lapse between the face identification sessions, the memory image that serves as the basis of identification loses its distinctive features, leading to resemblance-based errors when a person is mistaken for a similar-looking individual.Conclusion. It was found that the face identification procedure has to take into account a number of factors that can affect identification accuracy.